ANALISIS STRATEGI BADAN USAHA MILIK DESA (BUMDES) DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA LAMUNDE KEC. WATUBANGGA KAB. KOLAKA. - Alfika Alfika (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
In accordance with the mandate of Article 213 of Law number 32 of 2004 concerning Regional Government, villages can establish village-owned enterprises (BUMDes) to accommodate the economic activities of village communities. BUMDes is thus an umbrella for all economic activities in the Village. This means that BUMDes can accommodate all village economic activities, without having to create other economic business fields. Village-owned enterprises (BUMDes) are companies managed by the village community, whose management is separate from the village government. BUMDes was formed to explore the entrepreneurial potential that exists in the village. By being managed by community members who have an entrepreneurial spirit, it is hoped that BUMDes will later generate village original income obtained from the turnover of businesses managed by the BUMDes.The formulation of the problem from this thesis is: how is the BUMDes strategy in improving the economy of the village community Lamunde, Kec. Watubangga, Kab. Kolaka?The purpose of writing this thesis is to find out the BUMDes strategy in improving the economy of the community in Lamunde Village, Kec. Watubangga District, Kab. Kolaka. This type of research is seen from its object including field research conducted in the village of Lamunde, Kec. Watubangga, District. Kolaka. To obtain valid data, the authors used several data collection methods, namely documentation and interviews. Sources of data in.This research has two sources, namely primary data and secondary data. With regard to the analysis of data that has been collected, in this case the writer uses descriptive analysis using a qualitative approach. From the results of research on BUMDes strategies in improving the community's economy, namely by: BUMDes managers establish 4 business units including procurement of bagang, savings and loan business units (spp), shrimp ponds, raising cattle. In this case, since BUMDes